Occurrence, characterization, and transport mechanism of welding fumes particles emitted during the welding process - Norhidayah, Abdull; Nur Sarah Irina, Muhammad; Khairiah, Mohd Mokhtar; Zarifah, Shahri (Institute of Physics, 2024)
In metalworking processes, welding fumes are a prevalent type of particle aerosols. Particle characteristics, physical factors, and the generation process influence the transport of welding fumes in the air. This research delves into the investigation of welding fumes particles during two types of currents: low current (60A) and high current (130A). The study encompasses the determination of the occurrence and characterization of these particles, as well as estimating their transport mechanisms during the welding process. Direct reading instruments were utilized to measure the mass concentration and the number concentration of welding fumes particles alongside environmental parameters such as relative humidity, air velocity, and air temperature. The size distribution and morphology of the particles were collected through a sampling pump and subsequently analyzed using a Field Emission Scanning Electron Microscope (FESEM). Welding fumes particle transport was predicted by employing variables such as Reynolds number (Re), settling velocity, mechanical velocity, and stopping distance. The welding process's high current (130 A) generates a higher mass concentration (0.122mg/m3) than the low current (60 A) (0.064mg/m3). Notably, for particle size fractions ranging from 0.5μm to 2.0μm, the number of particles generated during high current surpassed that of low current, except for the 0.3μm size fraction. Analysis of the size distribution through FESEM revealed particle sizes of 2.25μm, 2.33μm, and 2.63μm for welding fumes collected during 130A. In contrast, fumes collected during 60A exhibited sizes of 0.45μm, 0.61μm, and 0.60μm. Notably, accumulation of particles were observed, indicating that the fumes collected during 60A consisted of smaller particles classified as fine particles. The particle counts for high and low currents were 283,232,661 count/m3 and 300,604,341 count/m3, respectively. The observed particle shapes appeared agglomerate, comprised of primary spherical particles adhering together through Van Der Waals forces. Reynolds number values (Re=0.0046-0.0223, less than 1) indicated that the motion of fume particles occurred within a laminar flow regime. Furthermore, the movement of particles was influenced by their diameter, with larger particles exhibiting higher settling velocities, smaller mechanical mobility, and shorter travelled distances. In summary, this research sheds light on the intricate transport mechanisms of welding fumes, providing insights into their occurrence, characterization, and transport during the metalworking process.